Determination of Trace Metals in Soil, Bean and Tomato Samples Collected from Agricultural Areas Near the Motorway in Tokat, Turkey - Gebeloglu, Naif; Camcicetin, Sema; Ece†, Ali; Sari, Hayati; Mendil, Durali; Tuzen, Mustafa (Asian Journal of Chemistry, 2016)
The concentrations of trace metals in the soil, bean and tomato samples collected from Tokat, Turkey have been determined by flame atomic absorption spectrometry after microwave digestion. Good accuracy was assured by the analysis of standard reference materials. The relative standard deviations for all measured metal concentrations were lower than 10%. Recovery values were nearly quantitative (≥ 95%). Metal accumulation factors were calculated for bean and tomato samples. The metal concentrations in samples were found to be 3.7–57.7, 1–15.3,5.6–68.8,4.2–517, 9.3–1020, 2.8–2890, 3356–9147, 818–4611 and 238–13956 μg/g for copper, lead, zinc, manganese, iron, sodium, potassium, calcium and magnesium, respectively.